2019
DOI: 10.32539/sjm.v2i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kecemasan dengan Nyeri Kepala Tipe Tegang pada Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya Angkatan 2013

Abstract: Nyeri kepala tipe tegang adalah nyeri kepala bilateral yang bersifat ringan hingga sedang, menekan, mengikat, disertai fotofobia atau fonofobia, tidak berdenyut, tidak dipengaruhi oleh aktivitas fisik, dan tidak terdapat mual atau muntah. Faktor risiko dari nyeri kepala tipe tegang bervariasi antara lain usia, jenis kelamin dan kecemasan. Mahasiswa kedokteran memiliki beban belajar yang cukup berat disertai kecemasan yang tinggi. Keadaan ini diduga memiliki hubungan dengan kejadian nyeri kepala tipe tegang. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…Most participants of this study had anxiety before receiving Quran recitation intervention (60%). This result was similar to study was performed by Wijaya, Sugiharto and Zulkarnain which found that 61.9% of medical students experience anxiety based on Hamilton Anxiety Rating Scale (HARS) (Wijaya et al, 2019). Nurrezki and Irawan also reported that 57.1% of medical students had anxiety based on Depression Anxiety Stress Scales (DASS) (Nurrezki & Irawan, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most participants of this study had anxiety before receiving Quran recitation intervention (60%). This result was similar to study was performed by Wijaya, Sugiharto and Zulkarnain which found that 61.9% of medical students experience anxiety based on Hamilton Anxiety Rating Scale (HARS) (Wijaya et al, 2019). Nurrezki and Irawan also reported that 57.1% of medical students had anxiety based on Depression Anxiety Stress Scales (DASS) (Nurrezki & Irawan, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the proportion of male participants who had anxiety was greater (77.8%) than women (55.6%). This result was different with the study conducted by Wijaya, Sugiharto and Zulkarnain that the proportion of anxiety in medical students batch 2013 of Universitas Sriwijaya was more common in female students (65.7%) than male students (53.3%) (Wijaya et al, 2019). Apriady, Yanis and Yulistini also reported in their study that anxiety symptoms were mostly found in female students (50.81%) than male students (38.27%).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Research in various countries about medical students revealed that there were more female medical students than male students with different ratios 13,14,15,16,17 . Female naturally have a caring and friendly attitude so they can communicate better with patients.…”
Section: Discussionmentioning
confidence: 99%